Reproductive performance of dairy cattle at Asella livestock farm, Arsi, Ethiopia. 1: indigenous cows versus their F1 crosses - Negussie, E.; Braennaeng, E.; Banjaw, K.; Rottmann, O.J. (Wiley, 1998)
In this study the reproductive performance of indigenous Ethiopian cows and their F1 crosses was evaluated and factors affecting reproductive performance were assessed, based on crossbreeding data collected from Asella Livestock Farm, Ethiopia. Age at first calving, number of services per conception, days open, gestation length and calving interval were considered in the evaluation of reproductive performance. Results obtained showed that genetic (breed) group was a significant source of variation for almost all of reproductive performance traits studied. First (F1) crosses were found to be better than the indigenous cows. Among the first crosses, Jersey crosses were the best. They had a lower age at first calving, required less number of services per conception, shorter days open and calving intervals than the rest of the genetic groups.